Peran Guru Dalam Mengintegrasikan Nilai-Nlai Perdamaian Pada Pembelajaran Sosiologi di SMA Negeri 5 Langsa - Fadilah Sari (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Sociology learning is very important in shaping the behavior of students in their lives. Because differences in views cause conflicts that occur in students. So that it causes problems of violence in the form of disputes, bullying, and brawls between students often occur. The purpose of this study is to determine the role of sociology teachers in integrating peace values ​​in sociology learning at SMA Negeri 5 Langsa. The research method used is a case study with a qualitative approach with data collection techniques through observation, interviews and document analysis. Research results The role of teachers at SMA Negeri 5 Langsa in integrating peace values ​​in the lives of their students. By using an inclusive, collaborative, and reflective approach, educators can build students who are sensitive to social problems and ready to help build a peaceful society. Therefore, sociology education not only helps us understand society, but also educates us to become people who value peace. Kata Kunci : The Role of Teachers, Integrating Peace Values , Sociology Learning